Introduction of a corporate security risk management system: The experience of Poland - Iryna Kalina; Viktoriia Khurdei; Vira Shevchuk; Tetiana Vlasiuk; Ihor Leonidov (Journal of Risk and Financial Management, 2022)
To ensure the economic security of companies, it is necessary to introduce a risk management system based on the use of various tools, especially financial ones. The purpose of the article is to scientifically substantiate the paradigm of integration of the risk management mechanism into the system of economic security in companies on the basis of risk-oriented management. The main study method was an online survey of 50 Polish companies in January-April 2021 using a developed questionnaire consisting of 40 questions. According to the results of the expert survey, it is determined that regardless of the type of economic activity of the enterprise, the main goal of introducing risk-oriented management is to preserve assets and increase the efficiency of financial and economic processes. The introduction of risk-oriented management is perceived as a tool to increase the value of the company and ensure the achievement of strategic goals. Fraud is a significant risk to the state of economic security for modern enterprises. To prevent the fact of fraud, taking into account the specifics of the operation of companies, it is suggested to conduct an annual examination. As a result, the suggested procedure should include an audit (audit of financial statements, forensics, transition to international financial reporting standards, audit of systems and processes), assessment (assessment for audit and reporting in accordance with international financial reporting standards, risk management assessment in accordance with international standards, assessment of the effectiveness of economic security), tax analytics (identification of tax risks, analysis of compliance with tax legislation, tax audit), and a due diligence procedure for investment objects.
Keywords: 650; risk management; investment; fraud; marketing tools; security